Recovery response of coenzyme Q10 to exercise-related physiological muscle damage, inflammation and oxidative stress: A systematic review - Yasul, Yavuz; Yılmaz, Busra; Yasul, Muhammet Enes; Şenel, Ömer; Cinar, Vedat (My University, 2024)
This systematic review aims to demonstrate that coenzyme Q10 (CoQ10) supplementation may be an effective molecule in improving exercise performance and recovering muscle damage, improving antioxidant capacity, and suppressing inflammatory processes. The study covers the literature in PubMed, Google Scholar, Web of Science and Scopus databases from 2011 to 2023. The final review was conducted on June 6. In the literature analysis, eight keywords (exercise, oxidative stress, CoQ10, muscle damage, inflammation, skeletal muscle, heart muscle, and performance) were employed to investigate the publications. The full texts of 362 full texts of articles were included in this study. These were analyzed according to the PRISMA reporting criteria. In the analysis, one study was conducted with experimental animals, two studies were conducted with male and female participants, and 12 studies were conducted with only male participants. Participants in twelve studies were well-trained. However, two studies were conducted with a sedentary group. In addition, CoQ10 supplementation was present in all studies. CoQ10 supplementation was between 5-60 mg/kg in 4 studies and 100 mg/kg and above in the remaining 10 studies. Antioxidant capacities and inflammation markers were among the parameters of most interest. There were fewer studies on skeletal and cardiac muscle damage and performance markers. CoQ10 supplementation during intense exercise elevates plasma CoQ10 and antioxidant levels while reducing inflammation markers. Additionally, it enhances contractile function in sarcomeres and cardiomyocytes. Nevertheless, additional studies are necessary to comprehensively as certain CoQ10 impact on athletic performance.
Keywords: Inflammation; oxidative stress; Antioxidant; coenzyme Q10; exercise performance; heart-skeletal muscle damage